Pengaruh Perceive Quality dan Country of Origin Terhadap Minat Beli Sepeda Motor Honda Vario - Aang Abdul Mugih; Reminta Lumban Batu (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the influence of perceived quality and country of origin on purchase intention for Honda Vario motorcycles. As a global brand, Honda holds a strong image, and consumers' perceptions of product quality and the country of origin are believed to significantly affect purchasing decisions. This research uses a quantitative approach with a survey method, and data were collected through questionnaires distributed to respondents who have considered or purchased a Honda Vario. The data were analyzed using multiple linear regression. The results indicate that perceived quality has a positive and significant effect on purchase intention. Country of origin also has a positive influence, although its effect is weaker compared to perceived quality. These findings suggest that perceived quality is the dominant factor in driving purchase intention, while the country of origin still plays an important role in shaping the overall brand image. The transportation and logistics sector plays a vital role in promoting national economic growth by serving as the main